1998
DOI: 10.1042/bj3300131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human red cell lysis by hypochlorous and hypobromous acids: insights into the mechanism of lysis

Abstract: Human red blood cells are lysed by the neutrophil-derived oxidant hypochlorous acid (HOCl), although the mechanism of lysis is unknown. Hypobromous acid (HOBr), a similarly reactive oxidant, lysed red cells approx. 10-fold faster than HOCl. Therefore we compared the effects of these oxidants on thiols, membrane lipids and proteins to determine which reactions are associated with lysis. There was no difference in the loss of reduced glutathione or membrane thiols with either oxidant, but HOBr reacted more readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 43 publications
4
61
0
2
Order By: Relevance
“…HOCl is cell permeable and reacts readily with thiols, thioethers and amino groups (11,12). Exposure of red cells or endothelial cells to HOCl results in an early decrease of the glutathione pool (13,14). This suggests that HOCl could modulate cell processes in a manner similar to that seen with H 2 O 2 or peroxynitrite.…”
mentioning
confidence: 83%
“…HOCl is cell permeable and reacts readily with thiols, thioethers and amino groups (11,12). Exposure of red cells or endothelial cells to HOCl results in an early decrease of the glutathione pool (13,14). This suggests that HOCl could modulate cell processes in a manner similar to that seen with H 2 O 2 or peroxynitrite.…”
mentioning
confidence: 83%
“…In other studies (data not shown), we observed a decrease in total numbers of microorganisms in seawater samples exposed to ozone that were stained with a nucleic acid stain and examined by epifluorescence microscopy or flow cytometry. Vissers et al (1998) explained the mechanism of human red cell lysis by hypobromous acid by stating that it reacts with membrane lipids and proteins. Ozone has been used for many years to maintain water quality in seawater aquaculture settings.…”
Section: Mechanisms For Removal and Inactivation Of Organismsmentioning
confidence: 99%
“…HClO treatment of erythrocyte membrane results in changes of membrane fluidity, surface area, and morphological transformations, events that precede cell lysis. 21,31,37 Our SEM observations showed that 50 µM HClO induced morphological alterations to the red cells, from a discoid to a spherocytic form. According to the bilayer couple hypothesis shape changes induced in erythrocytes by foreign molecules are due to differential expansion of the two monolayers of the red cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, because it readily reacts with a range of biological targets it has been difficult to identify which reactions are critical for its cytotoxic effects. 37 Human erythrocytes are a reliable and easily obtainable mechanism to detect oxidative stress. 11 Although the exact mechanism is not clear the cell membrane is considered the primary site for reaction.…”
Section: Discussionmentioning
confidence: 99%